2017
DOI: 10.1007/s11010-017-3206-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity effect of capsaicin on different types of skeletal muscle

Abstract: Capsaicin is a major pungent content in green and red peppers which are widely used as spice, and capsaicin may activate different receptors. To determine whether capsaicin has different effects on different types of skeletal muscle, we applied different concentrations (0, 0.01, and 0.02%) of capsaicin in the normal diet and conducted a four-week experiment on Sprague-Dawley rats. The fiber type composition, glucose metabolism enzyme activity, and different signaling molecules' expressions of receptors were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…We evaluated the effect of capsaicin on GSK3β phosphorylation in mouse myotubes and observed that capsaicin does not significantly affect GSK3β phosphorylation. This is in agreeance with previous work which reported that GSK3β phosphorylation was not affected by capsaicin administration in rat skeletal muscles [44].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We evaluated the effect of capsaicin on GSK3β phosphorylation in mouse myotubes and observed that capsaicin does not significantly affect GSK3β phosphorylation. This is in agreeance with previous work which reported that GSK3β phosphorylation was not affected by capsaicin administration in rat skeletal muscles [44].…”
Section: Discussionsupporting
confidence: 94%
“…Following glucose uptake in skeletal muscle cells, glucose molecules can be added to the glycogen chain for storage through glycogenesis or produce ATP during glycolysis [43]. Glycogen synthase kinase-3 β (GSK-3β) is a serine/threonine kinase that is involved in several biological processes including glucose and glycogen metabolism and insulin action in skeletal muscle cells [44]. Insulin inhibits the activation of GSK-3β through the PI3K/AKT pathway which subsequently promotes glycogen synthase (GS) activity and glycogen synthesis in skeletal muscle cells.…”
Section: Capsaicin Does Not Affect Phosphorylation Of Gsk-3β But Increases Atp Production In Mouse Myotubesmentioning
confidence: 99%
“…Succinate dehydrogenase staining was performed as previously described . Briefly, muscle sections (10 μM) were incubated in liquid (6 mM CaCl 2 , 0.3% glacial acetic acid, pH 4.4) for 10 min, flushed by Tris‐CaCl 2 eluent buffer (0.1 M Tris, 18 mM CaCl 2 ) twice, 1 min per flush, and then incubated in 37°C pre‐heated SDH eluent buffer (0.1 M sodium succinate, 0.18 mM tetranitroblue tetrazolium chloride (NBT), 0.81% N,N‐dimethylformamide, 0.23 M Tris, pH 7.4) for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism may contribute to the anti-osteoporotic effect of zoledronic acid, as well as the pain-relieving effect. Beneficial effects of zoledronic acid can be expected in skeletal muscle where TRPV1 channel appear to play a role in activating hypertrophic signaling and cytoprotection [51,52].…”
Section: Discussionmentioning
confidence: 99%